Environmental Biofilms as Reservoirs for Antimicrobial Resistance - Flores-Vargas, Gabriela; Bergsveinson, Jordyn; Lawrence, John R.; Korber, Darren R. (Frontiers in Microbiology, 2021)
Characterizing the response of microbial communities to a range of antibiotic concentrations is one of the strategies used to understand the impact of antibiotic resistance. Many studies have described the occurrence and prevalence of antibiotic resistance in microbial communities in reservoirs such as hospitals, sewage and farm feedlots, where bacteria are often exposed to high and/or constant concentrations of antibiotics. Outside these reservoirs, antibiotic concentrations are often lower, however the constant exposure to low concentrations of antibiotics may play an important role as chemical cues that contribute to antibiotic resistance. Low-level concentrations of antibiotics have not yet been broadly described in reservoirs outside of the aforementioned environments, nor has the transfer and dissemination of antibiotic resistant bacteria and genes within natural microbial communities. This review will focus on environmental reservoirs and mechanisms that are important in the maintenance and dissemination of antibiotic resistance: freshwater biofilms, agriculture-impacted environments, and bacteriophage composition. Such information may then be used to help identify most appropriate controls to minimize the global impact and to help preserve our supply of clinically relevant antibiotics.